PENGARUH UMUR POHON MELINA (Gmelina arborea Roxb) DAN PENAMBAHAN ADITIF PADA PROSES SULFAT TERHADAP SIFAT PULP - Rena M Siagian (Pusat Penelitian dan Pengembangan Hasil Hutan, 2002)
The investigation was aimed at assessing the influence of tree level of maturity and the amount of additive used in the sulphate cooking process on the properties of the corresponding resulting pulp. The trees selected in this regard were Gmelina arborea Roxb., consisting of four levels of maturities, i.e. 6, 8, 10 and 12 years. The additives used in the process were polysulfide (PS) and anthraqinone. The anthraquinone (AQ) was added 0.1 percent, without PS, and in the other cooking PS at 4.0 percent, without AQ. Meanwhile, this modified sulphate process was also conducted with any additive 4.0 percent PS and 0. 1 percent AQ. As a control. the sulphate cooking without both was carried out as well. Other cooking conditions were kept constant, i.e. active alkali 16 percent, sulphidity 25 percent, wood to liquor ratio 1 : 4, maximum temperature 170 °C. and total cooking durations 4 hours.The results revealed that the increase in tree maturity up to 10 years produced pulp with the highest yield. However. the pulp yield decreased when the maturity reached 12 years, which was the case when the pulp was obtained from the 6-years wood material. The use of 0.1 percent AQ additive did not improve the pulp yield but decreased the kappa number. The highest yield was obtained at 4. 0 percent PS additive, followed by the one using the combination of 4. 0 percent PS and 0.1 percent AQ.Melina wood from the corresponding 6 year old trees appeared technically suitable as raw material for pulp, since it strength was fairly high to meet the Indonesian National Standard (SNI) for the one from long-fibered softwood. Besides that. the use of additive improved the strength of pulp.